Shakespeare en miroir : Pierre Jean Jouve - Patrick Hersant (Etudes Epistémè)
Pierre Jean Jouve translated Shakespeare’s sonnets in 1955. The present paper tries to determine what this famous translation is worth, using Antoine Berman’s conceptual model as described in Pour une Critique des Traductions (1995). Starting with the pre-analytic reading of the translation, we then proceed to systematically list stylistic features in both the original and the translation, before describing Jouve’s « translational stance » and « horizon ». It appears that Jouve’s own poetics greatly influence, for better or worse, his work as a translator.